The role of nitric oxide synthase (nos) and the cofactor tetrahydrobiopterin (bh4) in diabetic cardiomyopathy - Duglan, D (2016)
The work presented within this thesis investigates the mechanisms which underlie the cardiovascular phenotype observed in a mouse model of type 1 diabetic cardiomyopathy. It demonstrates the protective effects of augmenting the NOS cofactor, BH4, to said cardiomyopathy, and explores the different pathways potentially involved in conferring protection. Chapter 1 summarises the current understanding of how hyperglycaemia triggers dysfunction in the vascular endothelium via the over-production of ROS. It describes the role of the NOS enzyme in both the vasculature and the myocardium, and the critical action of the BH4 cofactor to maintain NOS coupling and redox balance. The contribution of NOS "uncoupling" to diabetes pathophysiology is then discussed, examining the extent to which it has been implicated in the development of cardiomyopathy. Chapter 2 includes full descriptions of the materials and experimental techniques employed within this study. Chapter 3 investigates the role of neuronally-derived NO in the constrictor and dilator responses of rat resistance arteries. Organ bath experiments using wire myography and electrical stimulation reveal that NO released from perivascular neurons acts to oppose nerve-mediated vasoconstrictor responses in the rat mesenteric artery, in a frequency-dependent fashion. The perivascular localisation of nNOS is confirmed in rat and mouse mesenteric arteries with immunostaining, and the implications for nitrergic nerve dysfunction in diabetic neuropathy is discussed. Chapter 4 explores the function of the aorta and mesenteric arteries in the type 1 diabetic mouse, showing early impairment of endothelium-dependent vasodilatation in the aorta after 4 weeks of hyperglycaemia, which further persists after 12 weeks. This dysfunction in diabetes is associated with oxidative stress and indicative of NOS uncoupling, as evidenced by increased vascular superoxide production and a reduction in BH4 bioavailability. In contrast to the aorta, mesenteric vessels are protected from hyperglycaemic damage and do not show functional impairment. In these experiments, specific myocardial overexpression of the GCH1 transgene (to augment myocardial BH4) does not influence vascular outcomes, as expected. Chapter 5 examines the diabetic cardiomyopathy in vivo and in isolated cardiomyocytes, demonstrating significant LV diastolic dysfunction in WT diabetic mice, which precipitates only after 12 weeks and not as an early event. mGCH1 overexpression is able to improve LV performance in both control and diabetic hearts, accelerating cardiomyocyte relaxation and protecting against the development of LV dysfunction in the diabetic state. This dysfunction is associated with altered passive stiffness and changes to LV collagen content, but not with oxidative stress and NOS uncoupling as the principal driver. mGCH1 overexpression is able to improve LV mitochondrial ATP flux, increasing energy availability and potentially restoring metabolic flexibility to the heart in the setting of insulin insufficiency. The implementation of a 6-week oral BH4 supplement successfully elevates myocardial biopterin levels and NOS activity; whether this will provide protection against cardiomyopathy remains to be investigated. In contrary to mGCH1 overexpression, any potential mechanism is seemingly distinct from altered cardiomyocyte metabolism. Chapter 6 summarises the totality of the study findings, elaborating on potential signalling pathways mediated by BH4, as well as highlighting study limitations and directions for future work.